Influence of storage duration and density of raw cotton on the mechanics of the interaction process between feeding rollers in the cleaners of large impurities - Veliev, Fazil; Sailov, Rahib; Kerimova, Nurlana; Safarova, Tarana; İsmailzade, Mətanət and Sultanov, Elmar (Eastern-European Journal of Enterprise Technologies, 2018)
We have examined influence of storage duration and the density of cotton in bale on the adhesion between impurities and cotton. We found the effect of raw cotton storage, as well as the fiber, in a compacted state, which contributes to the more rapid penetration of weedy particles into the material. For raw cotton stored in a bale for 1 month, with a density of 150–200 kg/m3, the elements of large impurities interacted with fiber at an effort of 63–91 sN/g for leaf, stem, and bract; for small impurities – 714–1,000 sN/g. Upon cleaning, when only small impurities remain, this effort increased to 714–1,053 sN/g. These data correspond to the raw cotton of grade I. For grade III, the force of adhesion is slightly different: for large impurities – 76–96 sN/g, for small impurities – 714–1,267 sN/g; after cleaning – 857–947 sN/g. In a three-month storage in bale at a density of 250–300 kg/m3, the degree of interaction between impurities and fiber for the cotton of grade I was 109–137 sN/g, for grade III – 103–175 sN/g for large impurities. We have developed a technological mode that determines the multiplicity of cleaning; we also proposed a method for determining the spreading efforts that act on the feeding rollers and which are one of the most important factors for the process energy intensity. We analyzed the mechanics of the interaction process between a feeding roller blades and the transported layer of raw cotton. The results of research allow us to choose the required mode in the process of raw cotton cleaning from weedy impurities.